Changes in psychosocial work environment and depressive symptoms: A prospective study in junior physicians. Issue 12 (3rd September 2013) - Li, Jian; Weigl, Matthias; Glaser, Jürgen; Petru, Raluca; Siegrist, Johannes; Angerer, Peter
Abstract Background We examined the impact of changes in the psychosocial work environment on depressive symptoms in a sample of junior physicians, a high risk group for stress and mental disorders. Methods This is a three‐wave prospective study in 417 junior physicians during their residency in German hospitals. The psychosocial work environment was measured by the Effort–Reward Imbalance (ERI) Questionnaire at Waves 1 and 2, and the depressive symptoms were assessed with the State‐Trait Depression Scales at all three waves. Multivariate linear regression was applied for prospective associations between ERI across Waves 1 and 2, and baseline‐adjusted depressive symptoms at Wave 3. Results Compared with the ERI scores at Wave 1, at Wave 2, and mean scores between the two waves, the baseline‐adjusted ERI change scores between the two waves showed slightly better statistical power, predicting depressive symptoms at Wave 3 (β = 0.78, 95% CI = 0.38–1.18 for increased ERI per SD, β = 0.64, 95% CI = 0.22–1.06 for increased effort per SD, β = −0.65, 95% CI = −1.06 to −0.24 for increased reward per SD, and β = 0.68, 95% CI = 0.27–1.09 for increased overcommitment per SD). Conclusions Negative changes in the psychosocial work environment, specifically increased ERI, are associated with depressive symptoms in German junior physicians. Reducing the non‐reciprocity of working life, particularly improving reward at work, may have beneficial effects on prevention of mental health problems in the hospital workplace. Am. J. Ind. Med. 56:1414–1422, 2013. © 2013 Wiley Periodicals, Inc.